A valid and reliable test of technical skill for vision impaired football. Issue 1 (2nd January 2022) - Runswick, Oliver R.; Rawlinson, Alexander; Datson, Naomi; Allen, Peter M
ABSTRACT: Objectives: The International Paralympic Committee requires international federations to develop and implement sport-specific classification guidelines based on scientific evidence. Performance tests are key to developing new evidence-based criteria in football for athletes with vision impairment (VI). Therefore, the aim of this study was to develop a valid and reliable test of technical performance for VI football. Methods: To assure content and face validity, the Vision Impaired Football Skills (VIFS) test was based on recommendations from experienced players and coaches. To test construct validity, we compared 24 sighted football players split into two groups based on highest-level of performance but matched on experience. To test reliability participants completed the VIFS three times on two separate days. Results: Results supported construct validity through detecting differences in performance times between the two groups (p = .004, g = 1.28 95% CI = 0.41 - 2.15). Bias between visits (.54s ± 2.93s; 95% LoA = -5.21– 6.29) and intraclass correlations (.81, 95% CI = .56 - .92) showed between-day agreement and reliability. Within-day reliability was good after a familiarisation trial. Conclusions: Results support the suitability for the VIFS test for classification research. Future work should establish feasibility for players with a VI.